Mouths wide open: yawning as a communicative behavior in dogs - Hoff, Anna E., author; Nash, Donald J., advisor; Ackley, Steven R., committee member; Granger, Ben P., committee member (Colorado State University. Libraries, 2001)
Yawning is an action humans are very familiar with, yet this behavior is not unique to our species. Most vertebrate animals demonstrate yawning behavior. The cause of yawning is still uncertain, but yawns across vertebrate species seem to be concentrated around transitions between sleep and activity. Our most popular companion animal, Canis familiaris, also has periods of yawning before and after sleep. Dogs are naturally social living creatures and rely extensively on body language as a form of communication between group members. Behaviorists have suggested that some dog yawns are part of this visual communication system. The object of this observational study was to confirm that dogs have two main yawn types: a "rest" yawn that occurs between sleep-activity transitions, and a "social" yawn occurring during social interactions. Social interactions in this study referred to both dog-dog and human-dog interactions. Communicative yawning is performed to displace anxiety in an individual dog or to pacify aggression or excitement in other individuals. The frequency of rest yawns was predicted to be higher than that of social yawns. Both yawn types were morphologically the same, so the context of a yawn was used to indicate whether the yawn occurred for rest or communication. Even when recording the context of a yawn, distinguishing between displacement and pacification intentions was very difficult. Therefore, yawns motivated by displacement or pacification were collectively considered social in function. Because social yawns only occur in the presence of other individuals, dogs were observed in the social settings of dog daycare and obedience classes. Individual dogs were observed for 15-20 minutes. Some observations were videotaped, but the majority were taken in real time. Behaviors immediately preceding and following a yawn were recorded using an ethogram tailored to rest, displacement, and pacification behaviors. This study indicated that the majority of dog yawns occur during social interactions and not during sleep transitions. Using the yawn as a gauge to indicate if a dog is anxious or relaxed is one step towards more effective communication between dogs and humans. A yawn can act as a behavioral cue for dog handlers, trainers, owners and anyone concerned with canine welfare.
Keywords: Dogs -- Behavior; Yawning